MODEL-ELICITING ACTIVITIES DALAM MENGANALISIS KREATIVITAS PEMECAHAN MASALAH MATEMATIKA PADA MAHASISWA PENDIDIKAN MATEMATIKA DI PTKIN ACEH - Azhari, Budi; Irfan, Ade (Al-Khawarizmi, 2018)
This study aimed to know the components of the student creativity in problem solving that can be achieved through Model Eliciting Activities in preservice’s teacher of mathematics education of PTKIN in Aceh. This Research used qualitatif approach, since in this study want to describe the reality on the field namely data about the studets’ creativity in solving maths problem. The result showed that the componentsof flexibility obtained by contruction principle, the reality principle, and the self-just my assesment principle. Even so, there are student who got no flexibility with the third principle of the MEA, but only with the principles, the only reality MEA principle and the effective prototype principle. Mean while, the component of fluency is gained student by analysis of the construct documentation principle. The last component of creativity that is obtained through the construct shareability and reusability and the effective prototype principle. However there are students who do not obtain theses components due to the absence of new student-generated in carrying out problem-solving.